A general template for synthesis of hollow microsphere with well‐defined structure. Issue 3 (27th July 2012) - Gao, Ke‐Jing; Yi, Jianjun; Mao, Jing; Li, Guangtao; Xu, Bo‐Qing
Abstract Using chitooligosaccharides (COS) as the backbones and polycaprolactones (PCL) as the branches, a novel type of amphiphilic graft copolymers with a large amount of free OH and NH2 groups remained on the COS backbones was synthesized. The obtained Chitooligosaccharide‐graft‐poly(ε‐caprolactone)(COS‐g‐PCL) was self‐assembled into giant vesicles which served as templates for the preparation of hollow spheres of a series of metals(Au, Ag, Cu, Pt, and Pd). The method involved the initial mixing of COS‐g‐PCL and metal‐containing groups or metal ions to generate corresponding complex, followed by adding the selective solvent of water to induce the self‐assembly of the graft copolymers into giant vesicles; Metal ions were reduced and crosslinked by a subsequent calcination procedure to form metal hollow spheres. In addition, hybrid hollow spheres with fluorescent quantum dots and silica hollow spheres were also prepared by slightly modified procedures. A preliminary study on the trinitrotoluene sensor of CdS/vesicle hybrid hollow spheres revealed a considerable sensitivity, which exemplifies the distinct properties imparted by the hybrid hollow structure. All of the results demonstrate that the giant vesicles self‐assembled from COS‐g‐PCL could be utilized as effective templates for the synthesis of various hollow spheres. Using Chitooligosaccharide‐graft‐poly(ε‐caprolactone) vesicles as general templates, the hollow spheres of a series of metals such as Au, Ag, Cu, and Pt were produced. The method involved the initial absorption of metal ions from solution into the functional surface layer of the graft copolymer giant vesicles. Metal ions were reduced and crosslinked by a subsequent calcination procedure to form metal hollow spheres. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013